Ngaji Literacy Values In Forming Education Moderation Digital Era At The Pesantren - Aimah, Siti (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
The aim of this research is to find a model of literacy reading values in shaping the moderation of digital era education at the Pesantren Darussalam Blokagung. Using a qualitative approach with a case study type and a post-positivistic paradigm. The data collection technique is in-depth interviews. Participant observation and documentation. The data validity checking technique uses triangulation and data analysis uses three interactive models. It was found that the model of literacy recitation values at the Pesantren Darussalam Blokagung is patterned on the salaf as-shalih concept, namely al-muhaafadhatu alal-qadimiis-shalih wal-akhdu bil-jadiidil-ashlah, the substance of which is adaptive, innovative and competitive, meaning a new media for literacy recitation of the Koran. assessment-based perfecting the study method that is commonly used. Part of its adaptive and innovative nature is the use of applications such as offline and online Maktabah Syamilah in quickly searching for accurate sources in bahtsul masaail (study) activities in Islamic boarding schools, while the competition is the development of students' motivation in taking part in the study. kutubutturats and article writing competitions sourced from theal-Qur’an, Hadith and kutubutturats at national and international levels